2015
DOI: 10.1159/000441550
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Dopamine Receptor Genes in Vertebrates: Nine Subtypes in Osteichthyes

Abstract: Dopamine neurotransmission regulates various brain functions, and its regulatory roles are mediated by two families of G protein-coupled receptors: the D1 and D2 receptor families. In mammals, the D1 family comprises two receptor subtypes (D1 and D5), while the D2 family comprises three receptor subtypes (D2, D3 and D4). Phylogenetic analyses of dopamine receptor genes strongly suggest that the common ancestor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 42 publications
12
49
2
1
Order By: Relevance
“…In addition to the variation in neuronal connectivity that we reveal here, we have already demonstrated unexpected diversity of dopamine systems, despite their involvement in similar physiological/behavioral properties across vertebrate groups Yamamoto et al, 2015.…”
Section: Thalamocortical-like Functions By Midbrain Neurons In Teleosts?supporting
confidence: 51%
“…In addition to the variation in neuronal connectivity that we reveal here, we have already demonstrated unexpected diversity of dopamine systems, despite their involvement in similar physiological/behavioral properties across vertebrate groups Yamamoto et al, 2015.…”
Section: Thalamocortical-like Functions By Midbrain Neurons In Teleosts?supporting
confidence: 51%
“…The presence of two D2‐R paralogues in the eel probably results from the teleost specific whole genome duplication (3R) . Teleosts are known to possess more DA receptor genes compared to tetrapods . In the goldfish, three D2‐R genes were reported , although phylogenetical analysis suggests that the additional one, compared to the eel, may result from the specific tetraploidisation of this group .…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, three D2‐R genes were also isolated and initially named D2a, D2b and D2c , a nomenclature that we used in a previous study . However, they were renamed D2a, D2like and D2b, respectively, by Ensembl/ZFIN . Recent phylogenetical studies further showed that the zebrafish D2a and D2b are 3R‐duplicated genes, orthologous to the amniote D 2 , whereas the D2like would be an additional gene lost in tetrapods (renamed D8) .…”
Section: Discussionmentioning
confidence: 99%
“…All sequences match the specified targets using NCBI BLAST. The D1 receptor primer specifically targets the D1 A receptor subtype [Yamamoto et al, 2015], which is highly expressed in Area X and septum of zebra finches [Kubikova et al, 2010]; the D2 receptor primer targets the D2 receptor subtype of the D2 family (which also includes D3 and D4 receptors) [Yamamoto et al, 2015], which is expressed in VTA, Area X, and septum [Kubikova et al, 2010]. …”
Section: Methodsmentioning
confidence: 99%